2017
DOI: 10.1159/000480441
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Stage Migration Maximizes Survival Outcomes in Patients with Hepatocellular Carcinoma Treated with Sorafenib: An Observational Study

Abstract: Background: Level I evidence supports the use of sorafenib in patients with Barcelona Clinic Liver Cancer (BCLC) stage C hepatocellular carcinoma, where heterogeneity in efficacy exists due to varying clinicopathologic features of the disease. Aim: We evaluated whether prior treatment with curative or locoregional therapies influences sorafenib-specific survival. Methods: From a prospective data set of 785 consecutive patients from international specialist centres, 264 patients (34%) were treatment naïve (TN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…These patients showed a trend toward better PPS when treated with subsequent liver-directed or systemic treatment compared with BSC only (13 vs 5 months). These results are in line with post hoc analyses of the landmark phase III sorafenib trials and a recent international observational study [ 27 29 ], showing a clear survival benefit in strictly selected patients treated with sorafenib after TACE compared with those receiving BSC only [ 29 ]. Although sorafenib is the guideline-recommended treatment strategy after TACE failure [ 1 ], the predominantly intrahepatic pattern of progression at UTP (75%) implies that most patients may be candidate for both liver-directed (radioembolization) and systemic treatments (sorafenib).…”
Section: Discussionsupporting
confidence: 82%
“…These patients showed a trend toward better PPS when treated with subsequent liver-directed or systemic treatment compared with BSC only (13 vs 5 months). These results are in line with post hoc analyses of the landmark phase III sorafenib trials and a recent international observational study [ 27 29 ], showing a clear survival benefit in strictly selected patients treated with sorafenib after TACE compared with those receiving BSC only [ 29 ]. Although sorafenib is the guideline-recommended treatment strategy after TACE failure [ 1 ], the predominantly intrahepatic pattern of progression at UTP (75%) implies that most patients may be candidate for both liver-directed (radioembolization) and systemic treatments (sorafenib).…”
Section: Discussionsupporting
confidence: 82%
“…In clinical practice, in fact, a relevant time‐related migration of many HCC patients along different treatment strategies and tumour stages exist during their oncologic history . More importantly, both Vitale et al and Yen et al demonstrated an incremental benefit to overall survival from the sequential exposure to multiple lines of therapy, supporting the adoption of both, the therapeutic hierarchy and treatment stage migration strategies, in eligible patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, close follow-up must be performed for all patients. In the case of tumor recurrences, repeat resection, local ablation, TACE, radiation therapy, or systemic treatment [61] can be used based on the characteristics of tumor recurrences. For patients at high risk for tumor recurrence, postoperative TACE has been shown to be somewhat effective because it helps detect and control residual minimal intrahepatic cancer [62] (evidence level 4).…”
Section: Treatmentmentioning
confidence: 99%